1994
DOI: 10.1002/jcb.240550103
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear architecture supports integration of physiological regulatory signals for transcription of cell growth and tissue‐specific genes during osteoblast differentiation

Abstract: During the past several years it has become increasingly evident that the three-dimensional organization of the nucleus plays a critical role in transcriptional control. The principal theme of this prospect will be the contribution of nuclear structure to the regulation of gene expression as functionally related to development and maintenance of the osteoblast phenotype during establishment of bone tissue-like organization. The contributions of nuclear structure as it regulates and i s regulated by the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 74 publications
4
24
0
Order By: Relevance
“…In one possible model for MMTV transcription, MARs in both LTRs bind to the nuclear matrix and, as in models proposed for other transcriptional units (39,82), loop out the intervening transcribed region. Cux/CDP and SATB1 bind to the MAR-associated NREs in the MMTV LTR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In one possible model for MMTV transcription, MARs in both LTRs bind to the nuclear matrix and, as in models proposed for other transcriptional units (39,82), loop out the intervening transcribed region. Cux/CDP and SATB1 bind to the MAR-associated NREs in the MMTV LTR.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that binding to the nuclear matrix is a prerequisite for gene transcription and that MARs function to anchor genes to the nuclear matrix, a structure rich in transcription factors (39,82). In one possible model for MMTV transcription, MARs in both LTRs bind to the nuclear matrix and, as in models proposed for other transcriptional units (39,82), loop out the intervening transcribed region.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear matrix has been linked to multiple functions that mediate the control of gene expression within the nucleus (1)(2)(3)(4)(5)(6)(7)(8). This component of the nuclear architecture provides the internal scaffold of the nucleus; it consists of a peripheral lamina-pore complex, an internal filamentous ribonucleoprotein network, and residual nucleoli (2,8).…”
mentioning
confidence: 99%
“…Although specific MAR-binding proteins have been identified (18,77), their role in mediating the tissue-and cell-type-specific binding of active genes to the nuclear matrix is not understood. A number of transcription factors have been found to be associated with the nuclear matrix (6,73,76) and appear to differentially partition between the matrix and an extractable compartment of the nucleus, depending on such variables as tissue type and growth conditions (70). Therefore, it seems likely that specific mechanisms exist to regulate the exchange of transcription factors between the nuclear matrix and soluble compartments of the nucleus.…”
mentioning
confidence: 99%